2016
DOI: 10.3390/ijms17081370
|View full text |Cite
|
Sign up to set email alerts
|

MiR-132-3p Regulates the Osteogenic Differentiation of Thoracic Ligamentum Flavum Cells by Inhibiting Multiple Osteogenesis-Related Genes

Abstract: Ossification of the ligamentum flavum (OLF) is a disorder of heterotopic ossification of spinal ligaments and is the main cause of thoracic spinal canal stenosis. Previous studies suggested that miR-132-3p negatively regulates osteoblast differentiation. However, whether miR-132-3p is involved in the process of OLF has not been investigated. In this study, we investigated the effect of miR-132-3p and its target genes forkhead box O1 (FOXO1), growth differentiation factor 5 (GDF5) and SRY-box 6 (SOX6) on the os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Growth/differentiation factor 5 (GDF5) is a member of the transforming growth factor beta superfamily and was demonstrated to be closely related to the bone morphogenetic proteins (BMPs) (Baur et al, ; Nickel et al, ). A quite recent study showed that GDF5 and FOXO1 encourage the osteogenic differentiation of hLF cells (Qu et al, ). In this study, we also found that FOXO1 or GDF5 was being increased during the the osteogenic differentiation of hLF cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth/differentiation factor 5 (GDF5) is a member of the transforming growth factor beta superfamily and was demonstrated to be closely related to the bone morphogenetic proteins (BMPs) (Baur et al, ; Nickel et al, ). A quite recent study showed that GDF5 and FOXO1 encourage the osteogenic differentiation of hLF cells (Qu et al, ). In this study, we also found that FOXO1 or GDF5 was being increased during the the osteogenic differentiation of hLF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs were demonstrated to promote osteogenic differentiation, such as miR‐21 (Li et al, ), miR‐29b (Pan et al, ), and miR‐548d‐5p (Zhang et al, ). Some other miRNAs, miR‐132‐3p (Qu et al, ), miR‐143 (Li et al, ), miR‐145 (Jie et al, ), and miR‐221 (Yeh et al, ), were found to have a negative effect osteogenesis, which functioned mainly through targeting osteogenic genes, including runt‐related transcription factor 2 (RUNX2), Osterix, Wnt/β‐catenin, transforming growth factor beta (TGF‐β), or bone morphogenetic proteins (BMPs).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are other miRNAs that also target Sox6 in processes such as heart function regulation, 51 and osteogenic differentiation. 52 However, there are currently no studies that show the potential impact of miRNA/Sox6 regulatory pathway on the neural development-related process. Here, we found that both miR-96 and miR-467a-3p targeted the Sox6 to regulate NPCs induction from mESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are other miRNAs that also target Sox6 in processes such as heart function regulation,51 and osteogenic differentiation 52. Additionally, there are other miRNAs that also target Sox6 in processes such as heart function regulation,51 and osteogenic differentiation 52.…”
mentioning
confidence: 99%
“…Also, it has been demonstrated that ciRS-7 can repress Alzheimer’s disease (AD) development by suppressing NF-κB protein synthesis and inducing its cytoplasmic localization, promoting UCHL1 expression and UCHL1-induced amyloid precursor protein (APP) and BACE1 ubiquitination and degradation 13 . Moreover, primary ligament cells were preferentially used for transcription profiling in most OLF research 42, 43. In this study, for the first time, we used normal and ossified ligament tissues for transcription profiling, which reflect more closely the change in expression of ncRNAs and mRNA of OLF in vivo .…”
Section: Discussionmentioning
confidence: 99%